Kabahatler Kanununda Düzenlenen Kast, Taksir ve Hata Halleri Üzerine Bir İnceleme - (:unkn) unknown (My University, 2015)
2005 yılında yürürlüğe giren Türk Ceza Kanunuyla, ceza hukuku açısından birçok köklü değişiklik meydana gelmiştir. Kabahatler hukuku da bu süreçten etkilenmiş ve 765 sayılı eski Türk Ceza Kanununda yer alan kabahatlerin birçoğu 5326 sayılı Kanunla ayrıca düzenlenmiştir. Yeni Kabahatler Kanununun kabulüyle birlikte, artık Ceza Kanununda benimsenen genel hükümlerin, kabahatler açısından uygulama imkânı kalmamış ve kabahatler hukuku başlı başına bir disiplin halini almıştır. Bununla beraber, kabahatler hukuku multidisipliner bir alan olduğundan, ceza hukukuna ait bazı temel kavramların kabahatler açısından değerlendirilmesi gerekliliği doğmuştur. Bu kavramların başında, ceza hukukunda büyük önem atfedilen kast, taksir ve hata halleri gelmektedir. Kastın, taksirin ve hatanın; Kabahatler Kanununda nasıl düzenlendiği ve kabahatler açısından nasıl uygulama bulacağı çalışmanın konusunu oluşturacaktır. Ancak konunun daha iyi anlaşılabilmesi adına kabahat kavramı ve kabahatlerin genel yapısı üzerinde kısaca durulacaktır.

Numerous radical changes in terms of the penal code have been introduced by the Turkish penal code which has entered into force in the year 2005. Law of misdemeanor has also been affected by this process and many of the misdemeanors which were included in the former Turkish Penal Code no. 765 have also be regulated separately by the law no. 5326. The enforcement of the general provisions, which have been adopted by the penal code, from the point of view of the misdemeanors have become impossible along with the acceptance of the new law of misdemeanor, and the law of misdemeanor has become a discipline on its own. Since the law of misdemeanor is a multi-disciplinary field the need has arisen to evaluate some basic concepts belonging to the penal law from the point of view of misdemeanors. The concepts of deliberation, negligence and fault, to which great importance is attached in the penal code, are the most important ones of those concepts. This study aims at examining how the states of deliberation, negligence and fault are regulated by the law of misdemeanor and the manner in which they are applied from the point of view of misdemeanor. However we shall briefly touch upon the concept of misdemeanor and the general structure of misdemeanors for the sake of ensuring a better understanding of the subject.
A Study on Intent, Negligence and Fault Regulated by Misdemeanors Law
Keywords: Hukuk